Ideologias de linguagem e justiça: um estudo do caso Kaingang - Silva, Ana Luiza Martins (2023)
This work focuses on the right to use indigenous languages in criminal proceedings in Brazil, specifically, based on the analysis of a judicial process in progress at the 1st Federal Court of Erechim/RS, in which all defendants are indigenous people of the Kaingang people. The general objective of the research was to identify and problematize conceptions and ideologies of language mobilized for the rejection of the linguistic right of the defendants to translate the process and of interpreters in court, a situation that materializes the disjunction between the discourse of the law and its materialization in judicial processes and the consequent restriction of the possibilities of defense and communication of indigenous defendants. As a theoretical foundation, it articulated fields such as linguistic rights, language policies and language ideologies, in order to understand the counterpoints between the legal provisions that guarantee the right to language, translation and interpreters and their effective implementation. For this, it used the case study methodology and had as empirical material for analysis the texts of judicial decisions and other publicly available parts of the process. From the analysis of the empirical material, we realize that the Law agents based their speeches on nationalist, monolingual and graphocentric language ideologies, which reify a discrete, monolithic and static conception of language, which erases the complexity of real intercultural relations. Reflecting the heterogeneity of the society in which they circulate, the articulation of these language ideologies is triggered contingently and from divergent interests. In the case of the defense teams of the Kaingang defendants, the ideologies mobilize senses of authenticity and strategic essentialism to defend the linguistic rights of the indigenous defendants. These same ideologies operate, from the perspective of the Judiciary that judges the defendants' defense request, mobilizing assimilationist and integrationist meanings to support the assessment that the defendants speak Portuguese and, consequently, do not need the linguistic right of translation and interpreter in the course of the process. In addition to these findings, this case study allows us to problematize in a broader scope, which concern the field of law itself, in a complex and heterogeneous society, unequivocally founded on a racist and unequal structure.